The Intention of Millennial Generation in Paying Zakat through Digital Payments - Muhammad Daniyal Al Athar (International Journal of Islamic Business and Economics (IJIBEC), 2021)
The zakat management organization (OPZ) is currently making innovations in accordance with technological developments, namely by making it easier to pay zakat through digital payments. One of the groups of people who use digital payments is the millennial generation. Millennial generation is also known as the generation who likes things that are easy and related to technology. The purpose of this study is to analyze how the millennial generation intends to pay for ZIS through digital payments. The method used in this research is logistic regression. The results showed that the variable trust, perception variable and convenience variable had a significant influence on the intention of the millennial generation to pay ZIS through digital payments, while knowledge and motivation had an insignificant effect. This research has implications for OPZ to make android and ios-based applications to pay Zakat, infaq and shadaqoh..